2015
DOI: 10.3762/bjnano.6.175
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of carbon nanomembranes with helium ion microscopy

Abstract: SummaryCarbon nanomembranes (CNMs) prepared from aromatic self-assembled monolayers constitute a recently developed class of 2D materials. They are made by a combination of self-assembly, radiation-induced cross-linking and the detachment of the cross-linked SAM from its substrate. CNMs can be deposited on arbitrary substrates, including holey and perforated ones, as well as on metallic (transmission electron microscopy) grids. Therewith, freestanding membranes with a thickness of 1 nm and macroscopic lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…These imaging effects are related to the dielectric properties of the CNMs resulting in their electrostatic charging upon imaging with ions and thereby with a lower yield of secondary electrons reaching the detector of the HIM. [29] The presented examples demonstrate that the application of EUV-IL on the nanopatterning of CNMs results in perforated~1 nm thick molecular nanosheets and nanoribbons, which can be prepared as free-standing objects on holey supports. This methodology opens up manifold possibilities of implementing the supported or free-standing nanopatterned CNMs in devices such as nanomechanical, nanophotonic and nanoelectrical systems, as well as their integration into lateral heterostructures with other 2D materials, which will be presented in section 4 of this review.…”
Section: Free-standing Nanopatterned Cnmsmentioning
confidence: 81%
See 2 more Smart Citations
“…These imaging effects are related to the dielectric properties of the CNMs resulting in their electrostatic charging upon imaging with ions and thereby with a lower yield of secondary electrons reaching the detector of the HIM. [29] The presented examples demonstrate that the application of EUV-IL on the nanopatterning of CNMs results in perforated~1 nm thick molecular nanosheets and nanoribbons, which can be prepared as free-standing objects on holey supports. This methodology opens up manifold possibilities of implementing the supported or free-standing nanopatterned CNMs in devices such as nanomechanical, nanophotonic and nanoelectrical systems, as well as their integration into lateral heterostructures with other 2D materials, which will be presented in section 4 of this review.…”
Section: Free-standing Nanopatterned Cnmsmentioning
confidence: 81%
“…a) Large-area CNM with~1 nm thickness spanning a hexagonal metal grid. [29] b) Janus CNM on a metal grid with 16 nm gold nanoparticles immobilized on its S-face. [49] c) A van der Waals heterostructure consisting of four layers: (Janus CNM)/(C60-Janus CNM) 3 -spanning an orifice in a SiN membrane with dimensions of 40×44 µm 2 .…”
Section: Chemical Functionalization Of Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…a–c. It has been shown that CNMs with free‐standing areas of up to 0.3 mm 2 can be obtained in this way . Fig.…”
Section: Conversion Of Aromatic Sams Into Cnmsmentioning
confidence: 86%
“…It has the advantage of causing less charging artefacts and damage induced by the beam for small and delicate surface features than SEM. Furthermore, it does not require the sample to be as conductive or require gold coating , . So far, it has predominately been used to characterize biological samples, nanostructured polymers and for manufacturing nanostructures for nanoelectronics/energy storage , .…”
Section: Introductionmentioning
confidence: 99%